Pengaruh Return on Equity (ROE), Total Asset Turnover (TATO), Net Profit Margin (NPM) Terhadap Harga Saham : (Studi Empiris Pada Perusahaan Makanan dan Minuman Yang Terdaftar Di BEI Periode 2020-2024) - Putri, Zahra Adeliya Suharno; Fathihani; Sulistiyowati, Rini (HATTA : Jurnal Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
This study aims to analyze the Effect of Return on Equity (ROE), Total Asset Turnover (TATO), Net Profit Margin (NPM) on Stock Prices in food and beverage companies listed on the Indonesia Stock Exchange for the 2020-2024 period. The approach in this study is to use a quantitative approach, and based on the objectives, this type of research is causal. The independent variables in this study include Return on Equity (ROE), Total Asset Turnover (TATO), and Net Profit Margin (NPM) and the dependent variable in this study is Stock Price. The population in this study is food and beverage companies listed on the Indonesia Stock Exchange, totaling 27 companies for the 2020-2024 period. This study uses the Purposive Sampling method, selecting 18 companies multiplied by 5 periods, resulting in a sample size of 90 samples in this study. This study uses descriptive statistical analysis using secondary data with descriptive statistical tests. Continued with the classical assumption test using the multiple regression model hypothesis testing method. This study uses panel data regression tool analysis with the help of SPSS 26 application tools. The results of the study show that: (a) Return on equity (ROE) has a positive effect on share prices, (b) Total Asset Turnover (TATO) does not have an effect on share prices, (c) Net Profit Margin (NPM) has a positive effect on share prices.